Noisy Advertising and the Predation Rule in Antitrust Analysis - Hilke, John C.; Nelson, Philip B. (American Economic Review, 2016)
Can advertising by dominant firms pose a predatory threat? Theoretically, the answer clearly is yes. However, empirical evidence indicating the importance of this theoretical finding is largely missing. Economists' empirical studies of advertising, which typically focus on the question of whether high levels of advertising are indicative of the presence of a barrier to entry or signal that advertising information can substitute for consumption experience, usually employ average advertising levels that hide strategically focused price cuts or changes in short-term advertising rates.